Modeling of Type I and II hIMPDH (human Inosine monophosphate dehydrogenase) homotetrameric structure by Molecular Dynamics methods - DEEPAK K. MISHRA,; SUBRATA DASGUPTA,; BISHNU P. MUKHOPADHYAY,; SOUMITA MUKHERJEE, (International Journal of Pharma and Bio Sciences, 2016)
Inosine Monophosphate Dehydrogenase (IMPDH) is involved in the GMP nucleotide biosynthesis pathway and its isoform type II is produced in a large amount by the cancer and tumour cells. So, it is also considered as an attractive target for the development of anticancer agents. In vivo, the protein exists as homotetrameric unit but until now, a few monomeric and dimeric 3D low resolution X-ray crystal structures (having ~75%residues per monomer) of hIMPDH are available. On considering these aspects,attempt has been made to build the three-dimensional tetrameric model of both the isoforms of this enzyme by taking the initial monomeric/dimeric PDB structure of 1B3O (IMPDH-I) and 1JCN (IMPDH-II). Addition of missing ~25% residues followed by successive energy minimization and 10ns MD-simulation were followed for modeling of protein. The quality of final model structure has been validated by different modeling tools. The internal potential energy, stability and solvation free energy, 3D profile quality-index and Z-scores have indicated the goodness of final refined model of isoform I and II structures. Extensive comparative studies of the modelled structures reveal the differences in 3D conformation between tetrameric isoforms. The stereo chemical and conformational variations between type I and II may be exploited to design a better model inhibitor for IMPDH -II.